FILLING THE MARKET NICHE IN AGRITOURISM BY TAKING INTO ACCOUNT ALLERGEN-FREE MEALS - Anna Mazurek-Kusiak (Acta Scientiarum Polonorum. Oeconomia, 2010)
About two-third tourists arrive to an agritouristic farm with their families (namely with little children), thus the nutritional offer – that is the important component of a real product in agritourism – of these farms should be adjusted to that segment. There is another problem: according to European White Allergy Book, about 45–50% of little children and infants are food allergy sufferers. Such considerable percentage of nutritional allergies makes both little children and breastfeeding mothers must keep special diets. Unfortunately, only 6% of agritouristic farms located in Lublin region are able to offer nutrition for allergic people. The lack of special diets during the holiday stay is a serious barrier that makes the vacation or weekend in agritouristic farms impossible for families with allergic children. It forms a market niche that should be filled.